A STUDY OF RYCYCLE CONCRETE TO CONCERTED IN SUBBASE COURSE HIGHWAY MATERIALS - Traiyasut, Chokchai (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The purpose of this research is to study the behavior of lateritic-soil improved by Portland cement type 1 and recycle concrete for subbase course materials. The Sisaket province lateritic-soil sample were used and mixed with concrete recycle by 10 15 and 20 % by weight, and test were instead regarding to standard of highway testing of materials. The result was found that. The natural physical properties of lateritic-soil are as flowing, the plastic index value is 14.63 specific gravity is 2.75, maximum dry density using modified proctor compaction test is 2.24 gm/cm3, optimum moisture content is 5.90% and this soil is classified as GW (gravel) type. After that the lateritic-soil was improved by Portland cement type 1 with 5% by weight. The California bearing ratio (C.B.R.) found that. Every sample test are pass standard of highway subbase course materials and compressive strength vary on blow of compaction test, so that, there is a possibility to used concrete recycle into subbase course materials in highway construction.